Educational Dialogue of Prophet Ibrahim As with Prophet Ismail As in the Quran (Study Analysis of Qs As-Shaffat: 100-110) - Syamsu Nahar; Yusnaili Budianti; Rahmat Sukur (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This study aims to analyze: 1) the pattern of educational dialogue between Prophet Ibrahim As and Prophet Ismail As in QS As-Shaffat: 100-110, 2) How is the educational dialogue between Prophet Ibrahim As and Prophet Ismail As in QS As-Shaffat: 100- 110, and 3) the relevance of the educational dialogue between Prophet Ibrahim As and Prophet Ismail As in QS As-Shaffat with current family education. This study applies descriptive qualitative, in which the data collected qualitatively will be described through the study of revelation, while the research uses the maudhu'i interpretation method. in assessing the value of Islamic education in QS As -Shaffat this is what is right and appropriate. The study results show that: 1) The interaction pattern found in QS Ash-Shaffat verse 100 is a one-way pattern, where the communicator sends a message to the communicant in a dialogue. The educational dialogue pattern in QS As-Shaffat: 102 is said to be a two-way dialogue pattern (parent-child-parent pattern). In the two-way dialogue pattern, parents act as givers of action or recipients of the action. 2) The Main Educative Dialogue of Prophet Ibrahim As with Prophet Ismail As in QS As-Shaffat: 100-110 contains the purpose of education, educational materials, educational methods, educators with all their competencies, students, students with their academic ethics, and awards/ rewards. 3) The relevance of the educational dialogue between Prophet Ibrahim As and Prophet Ismail As in QS As-Shaffat: 100-110 with Current family education parents can build character when having dialogue with children, and the importance of parents in choosing the right language and communication techniques for children so that an efficient educational dialogue is established.